Ownership and Determinants Capital Structure of Public Listed Companies in Indonesia: a Panel Data Analysis - Hardiyanto, Arief Tri; Achsani, Noer Azam; Sembel, Roy; Maulana, Tb. Nur Ahmad (Universitas Prasetiya Mulya, 2013)
Capital structure is a mix of debts and equities used by a company to finance its investment. Debt offers benefit of tax shield from interest expenses that can be deducted in calculating company income tax. Unfortunately, company can not use debts in unlimited amount because it will lead to risk of bankcrupt. Therefore, company needs to establish a target (unobserved) capital structure which will optimize the value of the firm. The purpose of this study is to investigate the determinant of capital structure and ownership in public listed companies in Indonesia Stock Exchange using Time-Series CrossSection Regression (TSCSREG) and supported with a balanced panel data. Data used are financial statements of 228 public listed companies from group of eight industry sectors. Research finding confirms that tax shield and fixed financial burden are significantly influence the capital structure and state ownership also significantly influence the capital structure of the state owned enterprises.